PS 14-15 ACUTE WORSENING OF RENAL FUNCTION DURING DECONGESTIVE THERAPY IN PATIENTS WITH ACUTE DECOMPENSATED HEART FAILURE. (September 2016) - Amosova, Kateryna; Bezrodnyi, Andrii; Gorda, Igor; Sablin, Andrii; Melnychenko, Nataliya; Mostbauer, Galina; Kovaleva, Inna; Hodakivska, Elena; Bogdan, Stefan; Lazarev, Pavel; Prudkiy, Igor; Katsytadze, Igor
Abstract : Objective: To estimate clinical course and proximal hospital outcome in group of patients with early significant increase of NGAL as a marker of renal tubular injury. Design and Method: In our study we included 67 pts with «wet-warm» ADHF, and divided them in to 2 groups. Gr.1 - 16 patients with increase in NGAL on 3 day (D3) ≥ 20% from 1st day (D1), and Gr.2 - 51 patients without such increase. At baseline patients in gr.1 and gr.2 had no difference on NGAL and other clinical and laboratory parameters. Congestion endpoints were plasma NT-pro-BNP (ELISA) and mitral E/E' (TDI) at D3 and Dsc. Renal endpoints included acute kidney injury (AKI) (with AKI Network criteria of increase in serum creatinine of more than ≥26.4 mmol/l) during 48–72 hours, as well as eGRF (MDRD) and plasma NGAL at D3 and discharge (Dsc). Results: AKI developed in 15 (93, 8%) of patients of gr.1 and 2 (3, 9%) patients of gr.2. The length of hospital stay in gr.1 was 12, 9 ± 1, 1 vs 9, 1 ± 1, 2 days in gr.2, p < 0, 01. At 1-st day NT-pro-BNP was comparable increased in both groups (1291 ± 244 and 1232 ± 251 pg/ml, p > 0, 05, between gr.1 and gr.2 respectively) but on D3 it more significantly decreased in gr.2 - 822 ± 241 than in gr.1 - 1128 ± 237 pg/ml, p < 0, 05. Nevertheless on Dsc there was no significant difference between gr.1 - 825 ± 192 and gr.2 - 794 ± 184, p > 0, 05. Conclusions: In patients with ADHF active decongestive diuretic treatment is associated with transient deterioration of renal function during first days of staying at the hospital. It is accompanied by slower decongestion according to longer hospital stay and slower improvement of NT-pro-BNP and Mitral E/e[Combining Acute Accent]. But at the time of discharge there is no significant difference between these groups.